Interplay of Security, Privacy and Usability in Videoconferencing - Weinberger, Lydia; Eichenmüller, Christian; Benenson, Zinaida (Conference on Human Factors in Computing Systems - Proceedings, 2023)
In the period from August to October 2022, we conducted an online survey concerning users' perception and use of videoconferencing systems. We collected and analyzed a total of 245 responses from German-speaking participants. Each participant reported general use and case-specific use scenarios. We present usage trends and perceptions with respect to security, privacy and usability of various unified communications and collaboration (UCC) applications. The most frequently used tools, such as Zoom and Microsoft Teams, were rated lower in terms of security and privacy, but their usability ratings were above average. Tools tend to be avoided because of a lack of usability rather than security and privacy concerns. Nevertheless, almost 12% (29/245) of all participants reported using applications which were subject to security and privacy issues and which study participants would therefore personally prefer to avoid.
CRIS-Team Scopus Importer:2023-05-19
Keywords: online meetings; privacy; security; UCC; unified communication; usability; videoconferencing